Perancangan Database Sistem Informasi Dokter Praktik Mandiri (Si_Dori) - Lutfi Muhfidah; Anindya Khrisna Wardhani; Ega Nugraha (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
In the practice of independent doctors, patient registration is still done manually, so they have to come first because it takes longer, in addition, doctors cannot find out the disease experienced early and the follow-up actions that need to be taken. This study aims to make it easier for patients to register online, consult online, screen online, and have new features that make it easier for patients to access their conditions. The method used is the prototype method which is useful for designing and knowing the interaction between the system and the user, to be implemented by programmers. The results of this study are the design of an independent doctor's information system which includes a database design. The design of this independent doctor's information system can make it easier for patients to register online, consult online which can be given a prescription and redeemed at the nearest pharmacy, and more complete feature updates.